T‐Cell‐Derived Nanovesicles for Cancer Immunotherapy. Issue 33 (8th July 2021) - Hong, Jihye; Kang, Mikyung; Jung, Mungyo; Lee, Yun Young; Cho, Yongbum; Kim, Cheesue; Song, Seuk Young; Park, Chun Gwon; Doh, Junsang; Kim, Byung‐Soo
Abstract: Although T‐cell therapy is a remarkable breakthrough in cancer immunotherapy, the therapeutic efficacy is limited for solid tumors. A major cause of the low efficacy is T‐cell exhaustion by immunosuppressive mechanisms of solid tumors, which are mainly mediated by programmed death‐ligand 1 (PD‐L1) and transforming growth factor‐beta (TGF‐β). Herein, T‐cell‐derived nanovesicles (TCNVs) produced by the serial extrusion of cytotoxic T cells through membranes with micro‐/nanosized pores that inhibit T‐cell exhaustion and exhibit antitumoral activity maintained in the immunosuppressive tumor microenvironment (TME) are presented. TCNVs, which have programmed cell death protein 1 and TGF‐β receptor on their surface, block PD‐L1 on cancer cells and scavenge TGF‐β in the immunosuppressive TME, thereby preventing cytotoxic‐T‐cell exhaustion. In addition, TCNVs directly kill cancer cells via granzyme B delivery. TCNVs successfully suppress tumor growth in syngeneic‐solid‐tumor‐bearing mice. Taken together, TCNV offers an effective cancer immunotherapy strategy to overcome the tumor's immunosuppressive mechanisms. Abstract : T‐cell‐derived nanovesicles (TCNVs) are produced from activated CD8 + T cells for cancer immunotherapeutics. TCNVs exhibit inhibition of solid tumor growth through blocking immunosuppressive molecules in the tumor microenvironment, aiding in maintaining the cytotoxic T cells' antitumor activity. Moreover, TCNVs kill tumor cells directly. Therefore, TCNV offers an effective cancer immunotherapy strategy to overcome the solid tumor's immunosuppressive mechanisms.